Pregnancy in scar form previous cesarean section: surgical challenge in its outcome - Del Aguila-Salgado, Karina Roxana (2024)
Pregnancy in the cesarean scar consists of the implantation of the blastocyst inthe scar tissue of a previous cesarean section. Timely diagnosis allows therapeuticpossibilities. Inadequate management or expectant management may be related toadverse outcomes. Its therapy should be oriented to the resection of the ectopicpregnancy according to maternal conditions and reproductive desires. We reporta case of pregnancy in a previous cesarean section scar treated at the HospitalNacional Dos de Mayo, Lima, Peru.